Perubahan Karakter Tokoh Utama Suar dalam Novel Catatan Juang Karya Fiersa Besari: Psikologi Behaviorisme - Dinnata, Thoriq Furqon; Lubis, Haris Sutan; Marsella, Emma (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the changes in the character of the main character Suar in the novel Note Juang by Fiersa Besari which is related to the reality of life. Changes in the character of the main character are examined using the theory of behaviorism of Frederic Skinner which proposes behaviorism which includes three aspects, namely, stimulus, response, and effect. This research employs a qualitative approach to generate descriptive data in the form of written words from the observed subjects. The data source comes from the novel Catatan Juang by Fiersa Besari published in 2017 by Kepustakaan mediakita with a total of 306 pages. The data taken is in the form of words, phrases, clauses, and paragraphs that refer to changes in the character of the main character. The techniques used use documentation techniques or literature studies followed by recording techniques. When all the data is collected, the next process is data analysis, which involves data reduction, data presentation, and then drawing conclusions. The research findings indicate that the main character, Suar, has indeed undergone a transformation in character Initially melancholic, introverted, and closed off, Suar has now become more cheerful, caring towards others, extroverted, and eager to try new things ultimately, Suar's life aligns with her long-held dreams